Podatek rolny w relacji do zasobów czynników wytwórczych gospodarstw rolniczych - Chmielewska, Marzena (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2009)
The paper presents relations between agricultural tax and chosen production resources in agricultural farms. The highest relation between agricultural tax and cropland area in 2006 recorded in all voivodships. The relationship between agricultural tax and possessed equity capital was comparatively low. Therefore, it could be ascertained that agriculture tax was relatively small tax burden for farmers and did not contribute to their activity production strategy. Most of farmers were against the implementation of income tax instead agriculture tax.